2007
DOI: 10.1176/appi.ajp.2007.06111886
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Antipsychotic Administration During Late Pregnancy: Placental Passage and Obstetrical Outcomes

Abstract: All four antipsychotics demonstrated incomplete placental passage. Quetiapine demonstrated the lowest placental passage of the medications studied. These novel data provide an initial quantification of the placental passage of antipsychotics and fetal exposure in humans, demonstrating significant differences between individual medications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
175
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 217 publications
(183 citation statements)
references
References 14 publications
3
175
0
5
Order By: Relevance
“…Olanzapine has an in vivo placental passage ratio of 72.2% [Newport et al 2007], and several case reports on its use have described uneventful pregnancies and healthy infants. The largest study to date found that olanzapine did not increase the risk of major congenital malformations, but was associated with a higher maternal BMI, maternal gestational diabetes and low birth weight [Reis and Kallen, 2008].…”
Section: Commentsmentioning
confidence: 99%
“…Olanzapine has an in vivo placental passage ratio of 72.2% [Newport et al 2007], and several case reports on its use have described uneventful pregnancies and healthy infants. The largest study to date found that olanzapine did not increase the risk of major congenital malformations, but was associated with a higher maternal BMI, maternal gestational diabetes and low birth weight [Reis and Kallen, 2008].…”
Section: Commentsmentioning
confidence: 99%
“…72,83 Quetiapine had the lowest placental passage compared with the three medications mentioned above. 84 Despite their limitations, the available studies did not demonstrate an elevated risk. 73 The rate of malformations after fetal exposure to quetiapine is about 3.5%.…”
Section: Congenital Malformationsmentioning
confidence: 95%
“…A lack of difference between exposed and non-exposed women has been reported for mean birth weight 71,74,77 and proportion of small for gestational age infants. 74 Moreover, the risk of low birth weight 71,72,84 or proportion of small for gestational age infants was not reported to increase for exposed women. 85 Some authors showed that typical antipsychotics but not SGAs were associated with lower mean birth weight of fetus.…”
Section: Other Neonatal Outcomesmentioning
confidence: 96%
See 1 more Smart Citation
“…Various factors may further contribute to negative birth outcomes such as, the use of medications during pregnancy, the mother's stress level in low-income population, nutritional status, chronic diseases, acute diseases, illicit drug use, domestic violence, depression and environmental factors [14][15][16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%